2018
DOI: 10.1097/nmd.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Predicts Social Functioning in Clinically Stable Patients With Bipolar Disorder

Abstract: The current study focused on the association between resilience and social functioning in patients with bipolar disorder (BD). Forty clinically stable patients with BD type I and BD type II, as well as 40 healthy controls, matched for age, sex, and educational background were enrolled. Clinical status was assessed by the Montgomery-Åsberg Depression Rating Scale and the Young Mania Rating Scale. Functioning was evaluated by the Mini International Classification of Functioning, Disability and Health rating of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Resilience was not directly associated with QoL or with work and psychosocial functioning impairment, in contrast to previous findings (Bozikas et al, 2018;Hofer et al, 2017). It should be noted that the present study used a BD-specific resilience measure that allowed us to analyze the differential effects of separate resilience components in syndromic patients, thereby advancing knowledge of protective factors during bipolar episodes, unlike previous research analyzing generic resilience in subsyndromal bipolar patients (Bozikas et al, 2018;Hofer et al, 2017).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Resilience was not directly associated with QoL or with work and psychosocial functioning impairment, in contrast to previous findings (Bozikas et al, 2018;Hofer et al, 2017). It should be noted that the present study used a BD-specific resilience measure that allowed us to analyze the differential effects of separate resilience components in syndromic patients, thereby advancing knowledge of protective factors during bipolar episodes, unlike previous research analyzing generic resilience in subsyndromal bipolar patients (Bozikas et al, 2018;Hofer et al, 2017).…”
Section: Discussionmentioning
confidence: 62%
“…). Previous studies have evidenced that individuals with BD and high levels of resilience reported better outcomes in recovery, QoL (Echezarraga et al, 2018;Lee et al, 2017), and psychosocial functioning (Bozikas et al, 2018;Echezarraga et al, 2018) compared to individuals with high BD and low levels of resilience. Specific resilience factors, such as self-care, self-confidence, and interpersonal support, have been reported by individuals who no longer present symptoms of BD as essential ingredients for their recovery .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Bozi ka s et a l ., 2018, Greece 19 To exa mi ne the a s sociation between res ilience a nd social functi oni ng i n pa ti ents wi th BD. 40 cl i nically s table pa ti ents wi th BD type I a nd BD type II were i ncl uded.…”
Section: /7 Yesmentioning
confidence: 99%